Exploring neurocognitive sequelae following mild traumatic brain injury and the effects that it has on school readiness. - Billing, Ashné Courtney (My University, 2018)
Literature reveals controversial issues surrounding Mild Traumatic Brain Injury (Mi-TBI) and the possible latent effects that follow and whether it impacts on the cognitive profile required for effective scholastic performance. Mi-TBI Test and Neurotypical contrast participants, aged 6-10 years, were recruited from Chris Hani Baragwanath Academic Hospital (CHBAH). The Aptitudes Test for School Beginners (ASB) was used to elicit participant’s cognitive profile. Across the cognitive profile, the performances delivered by the combined Mi-TBI sample were weaker than that delivered by the neurotypical comparison group, specifically on memory and verbal comprehension subtests. Further interrogation of the realized data was attempted through subclassification of Mi-TBI participants who were dependent on whether or not CT scans were conducted and what the results of those were. However, results of this interrogation proved to be inconclusive. Other analysis such as correlation and regression tests reveal that age, grade and grade repetition were significantly correlated to the cognitive profile for school readiness, while only grade and preschool attendance significantly predicted the cognitive profile for school readiness. Furthermore research is needed in this field to validate these results and add to the body of literature.
A research report submitted in a partial fulfilment of the requirements for the Master of Arts (Social and Psychological Research) degree to the Faculty of Humanities in the field of Research, University of the Witwatersrand, Johannesburg, August 2018
Keywords: Brain damage; Brain damage--Patients--Rehabilitation